Learning from the Armed Conflict Between India and Pakistan: Is Nuclear Weapons Necessary? - Siraj, Adnan; Khan, Shah Rukh; Jabbi, Yusupha (Uti Possidetis: Journal of International Law, 2025)
Background: The nuclearization of South Asia poses a long-term threat to the regional and global security. The long-standing rivalry between India and Pakistan is dangerously compounded by their opposing nuclear doctrines, and hence an analysis of their strategic stability is an imperative. Methodology: This study uses the methodology of comparative analysis and analysis of the nuclear postures of India and Pakistan in the context of modern deterrence theory and international law. The analysis rests on empirical evidence from past crises up to the time of the 2025 escalation to gain real world credibility of the doctrines. Objectives:The purpose of this paper is to dissect India's 'No First Use' policy vis-a-vis Pakistan's 'Full-Spectrum Deterrence' and first use ambiguity. It aims to examine how these contrary doctrines contribute to escalation and whether they comply with international legal norms. Findings: The analysis illuminates a critical "stability-instability paradox," in which nuclear weapons prevent total war but lower the threshold for limited conflict. Inconsistencies such as India's massive retaliation vow against Pakistan's tactical nuclear weapons add dangerous pressures to escalation. This asymmetry and poor communication with crisis lead to a very volatile security environment. Originality/Novelty: The novelty of the paper is the integration of the deterrence theory with international law and its application to contemporary empirical data such as the 2025 crisis. It contends that current nuclear postures, far from being stabilizing, have opened new avenues to war, calling conventional wisdom on deterrence into question.